1981
DOI: 10.2190/64ey-qlw8-765a-k0kh
|View full text |Cite
|
Sign up to set email alerts
|

Images of the Psychotherapist: A Theoretical and Methodological Perspective

Abstract: This paper presents a theoretical and methodological approach to studying the ways in which psychotherapy patients create and interpret mental representations of their therapists and the psychotherapeutic process both during therapy and after termination. A network of measures, The Therapist Representation Inventory, was developed to specify the interrelationships between the stylistic, functional and formal properties of such symbolic evocations across different states of consciousness and in different situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
1
12

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 17 publications
8
85
1
12
Order By: Relevance
“…This factor reflects the extent to which therapists are able to visualize patients' facial expressions and gestures. This factor structure essentially replicates that obtained in previous studies of both patients' and supervisees' representations of their therapists and supervisors, respectively (Geller et al, 1982;Geller & Schaffer, 1992).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This factor reflects the extent to which therapists are able to visualize patients' facial expressions and gestures. This factor structure essentially replicates that obtained in previous studies of both patients' and supervisees' representations of their therapists and supervisors, respectively (Geller et al, 1982;Geller & Schaffer, 1992).…”
Section: Resultssupporting
confidence: 84%
“…Previous research has indicated that patients (e.g., Geller et al, 1982; and therapists-in-training (e.g., Geller & Schaffer, 1992) bring into awareness the felt presence of their therapists and their supervisors primarily through imagistic (visual and auditory) and lexical means. It is not surprising, therefore, that therapists tend to rely more heavily on visual and lexical modes of representation, rather than on an experiential-intuitive mode, when thinking about their patients between sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such negative emotional experiences reflected clients' dependency fears, anxiety, and sadness. Geller et al (1981) described clients who were unable to internalize the therapist as a benignly influential other, as well as clients who mourned the loss of the therapist, either between sessions or after termination. The inability to internalize the therapist as a benign other may be reflected in those clients who expressed fears of being dependent, as well as in those who experienced anxiety.…”
Section: Clients' Affective Response To Internal Representationsmentioning
confidence: 99%